2015
DOI: 10.1002/biot.201400395
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane vesicles as platform vaccine technology

Abstract: Outer membrane vesicles (OMVs) are released spontaneously during growth by many Gram‐negative bacteria. They present a range of surface antigens in a native conformation and have natural properties like immunogenicity, self‐adjuvation and uptake by immune cells which make them attractive for application as vaccines against pathogenic bacteria. In particular with Neisseria meningitidis, they have been investigated extensively and an OMV‐containing meningococcal vaccine has recently been approved by regulatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
252
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(264 citation statements)
references
References 186 publications
(308 reference statements)
4
252
0
8
Order By: Relevance
“…Recent advances in bacterial engineering allow for the customization of OMVs (van der Pol et al, 2015). Strategies include the introduction of heterologous proteins in OMVs as well as retaining antigens which normally undergo proteolytic processing and are released from the bacterial membrane (Kuipers et al, 2015; van der Pol et al, 2015). The effectiveness of complement evasion molecules in vaccines is proven by N. meningitidis fHbp and B. pertussis FHA (Santolaya et al, 2012; Locht, 2016).…”
Section: Complement Evasion Molecules As Vaccine Targetsmentioning
confidence: 99%
“…Recent advances in bacterial engineering allow for the customization of OMVs (van der Pol et al, 2015). Strategies include the introduction of heterologous proteins in OMVs as well as retaining antigens which normally undergo proteolytic processing and are released from the bacterial membrane (Kuipers et al, 2015; van der Pol et al, 2015). The effectiveness of complement evasion molecules in vaccines is proven by N. meningitidis fHbp and B. pertussis FHA (Santolaya et al, 2012; Locht, 2016).…”
Section: Complement Evasion Molecules As Vaccine Targetsmentioning
confidence: 99%
“…Many studies with Gram-negative pathogens conducted in the last decade have shown that MVs are internalized in host cells and contribute to virulence by delivering cytotoxic factors as well as mediators that interfere with the immune system [4,5]. When first discovered, MVs from pathogenic bacteria were proposed as vaccines, and research in this field continues [68]. Promising novel therapy applications include using engineered MVs expressing antigens from pathogenic strains or as specialized drug delivery vehicles [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Hypervesiculating mutants can produce atypical MVs, which may have surface antigens with a different conformation or display altered immunogenicity, self-adjuvation, or uptake by host cells. The variability caused by these features can affect studies evaluating the application of MVs in different fields [810]. …”
Section: Introductionmentioning
confidence: 99%
“…Outer membrane vesicles (OMVs) are naturally generated by all gram‐negative bacteria during their growth . Gram‐positive bacteria, mycobacteria, and archaea can also naturally release OMVs.…”
Section: Outer Membrane Vesicle Vaccines Generalized Modules For Memmentioning
confidence: 99%